2020
DOI: 10.21203/rs.3.rs-40977/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initial predictors for short-term prognosis in anti-melanoma differentiation-associated protein-5 positive patients

Abstract: Background: Anti-melanoma differentiation-associated protein-5 (anti-MDA5) positive patients are characterized by the high mortality rate caused by interstitial lung disease (ILD). We conducted a retrospective study to summarize the clinical features and identify the initial predictors for death in anti-MDA5 positive patients.Methods: We designed a retrospective cohort of anti-MDA5 positive patients. The demographic and clinical data recorded on first admission, as well as the outcomes during the first six mon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
11
2
Order By: Relevance
“…Previous reports shows the correlation of high-level serum ferritin and KL-6 with poor prognosis in anti-MDA5-DM (2,4), whereas no signi cant difference was detected in our study. Bivariate correlation analysis reveals a close correlation of ferritin with LDH and albumin.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Previous reports shows the correlation of high-level serum ferritin and KL-6 with poor prognosis in anti-MDA5-DM (2,4), whereas no signi cant difference was detected in our study. Bivariate correlation analysis reveals a close correlation of ferritin with LDH and albumin.…”
Section: Discussioncontrasting
confidence: 95%
“…Interstitial lung disease (ILD) is a major cause of death in patients with DM. When rapidly progressive ILD (RPILD) occurs, the mortality rate is signi cantly increased (1)(2)(3)(4)(5). Although not completely understood, data suggest that the pathogenesis of ILD in anti-MDA5-DM may be different from other types of DM(6).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, another case-control research reported that an elevated serum KL-6 was with negative correlation with FVC% and forced expiratory volume in the first second (FEV1%) (r = −0.93, r = −0.91, respectively) (12). On the other hand, a recent study reported the HRCT ground-glass opacity (GGO) score ≥4 (HR 4.8; 95% CI, 1.3-17.9), KL-6 >1,600 U/ml (HR 3.7; 95% CI, 1.5-9.1) were identified as independent predictors for progressive ILD (48). To some extent, the elevated KL-6 concentrations may have consistency with the progressive lesion of HRCT under the inflammatory storm.…”
Section: Discussionmentioning
confidence: 99%
“…(AE-ILD: n = 112, Stable ILD: n = 298). Additionally, adjusted HR (95%CI) of estimating the mortality about ILD were collected from 10 studies(13,15,21,24,26,37,40,42,48,50), and also adjusted HR (95%CI) of estimating progression of ILD were collected from five studies(17,21,28,40,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation